Dominica. Significant Achievements 2020 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2021)
The main activities carried out by the Institute in Dominica during 2020 are identified, with respect to the needs and interests of the country, identifying problems in family farming, food security and agricultural planning. Likewise, among the achievements carried out, the progress of the different projects implemented, the extension activities in the dissemination of information with publications, forums, training and research are recognized. Finally, for the recovery of the rural sector due to post-COVID-19, support was provided to develop an agricultural policy framework that will promote the transformation of the agricultural sector, with a focus on building climate resilience.